PERANAN INSENTIF TERHADAP EFEKTIVITAS KERJA PEGAWAI DI UPT DINAS PENDIDIKAN KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - Andini, Riyal (PREDIKSI, 2015)
ABSTRACTÂ The purpose of this study was to determine the effect of causation between the incentive to improve the effectiveness of employees working at the Department of Education's Office District of Anggana UPT KutaiKartanegara District. Therefore, we propose the hypothesis in this study as follows: